DESKRIPSI KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA PADA MATERI BANGUN DATAR DI SMP - Hidayat Aspiandi; Zubaidah Zubaidah; Asep Nursangaji (Universitas Tanjungpura, 2020)
Abstract Students mathematical problem solving abilities are one of the most important aspects that students must master at the basic stage in learning mathematics. This study aims to describe students mathematical problem-solving abilities in flat shapes. The subjects in this study were students of class VII SMP Negeri 1 Jawai. The data collection techniques used were direct communication and test techniques. The results obtained were the high mathematical problem solving ability of 20%, the students mathematical problem solving ability was 64% and 16% of the students had low mathematical problem solving abilities. In general students mathematical problem solving abilities are in the medium category. Students mathematical problem solving abilities differ from each indicator of problem solving abilities namely students ability to understand problems, students ability to plan, students ability to implement solving plans, and students ability to re-examine. Keywords: Description, Mathematical Problem Solving Ability, Build Flat.